1997
DOI: 10.1104/pp.113.4.1041
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of a Ripening-Specific Lipoxygenase and Its Expression during Wild-Type and Mutant Tomato Fruit Development

Abstract: A 94-kD protein that accumulates predominately in tomato (Lycopersicon esculenfum) fruit during ripening was purified, and antibodies specific for the purified protein were used to isolate cDNA clones from a red-ripe fruit cDNA library. A sequence analysis of these cDNAs and cross-reactivity of the 94-kD-specific antibodies to the soybean lipoxygenase (LOX) L-1, L-2, and L-3 proteins and soybean LOX L-l-specific antibodies to the 94-kD protein identified it as a member of the LOX gene family. Maximum levels of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
27
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 60 publications
(31 citation statements)
references
References 40 publications
(55 reference statements)
1
27
0
2
Order By: Relevance
“…3 Hisar Safeda suggest that membrane deterioration and hence loss of membrane integrity and tissue structure is much faster in soft variety than in the firm one. Membrane deterioration due to increased LOX activity has been reported to be responsible for loss of tissue structure in saskatoon, avocado, pear and tomato fruit during ripening (Kausch and Handa, 1997;Rogiers et al, 1998;Mondal et al, 2004;Liu et al, 2008). Lurie and Ben Arie (1983) demonstrated increased lipid peroxidation in ripening apple and attributed this to increase in LOX activity.…”
Section: Indices Of Lipid Peroxidationmentioning
confidence: 99%
“…3 Hisar Safeda suggest that membrane deterioration and hence loss of membrane integrity and tissue structure is much faster in soft variety than in the firm one. Membrane deterioration due to increased LOX activity has been reported to be responsible for loss of tissue structure in saskatoon, avocado, pear and tomato fruit during ripening (Kausch and Handa, 1997;Rogiers et al, 1998;Mondal et al, 2004;Liu et al, 2008). Lurie and Ben Arie (1983) demonstrated increased lipid peroxidation in ripening apple and attributed this to increase in LOX activity.…”
Section: Indices Of Lipid Peroxidationmentioning
confidence: 99%
“…LOX activities have been identified in a wide range of organisms, tissues, and developmental stages and have been implicated in a variety of processes including regulation of plant development, fruit ripening, plant senescence, disease, and pest resistance (Kolomiets et al 2001;Zhang et al 2006;Chen et al 2004). The role of the LOX pathway in the biosynthesis of fruit aroma compounds has already been reported for tomato (Kausch and Handa 1997), olive (Salas et al 2000), bell pepper (Matsui et al 1997), apple (Rowan et al 1999), citrus fruit (Gomi et al 2003), and strawberry (Perez et al 1999). LOX proteins are classified into two groups depending on their ability to oxygenate the carbon chain at position 9 (9-LOX) or 13 (13-LOX).…”
Section: Collocation Of Major Qtls and Candidate Genesmentioning
confidence: 99%
“…In plants, linoleic acid and linolenic acid are initially oxygenated to form 9(S)-hydroperoxy or 13(S)-hydroperoxy linolenic acid by LOX and are then metabolized into a number of biologically active compounds (Feussner and Wasternack 2002). Many studies have suggested that LOXs play a crucial role in plant evolution including growth and development, flowering, fruit ripening, seed germination and senescence (Saravitz and Siedow 1995;Ye et al 2000;Kausch and Handa 1997;Sung and Chiu 1995;Rouet-Mayer et al 1992;Fukuchi-Mizutani et al 2000). In particular, LOX-derived products such as JA, methyl jasmonate (Me-JA), and tuberonic acid glucoside (TAG) have been suggested to play important role in potato tuberization (Pelacho and Mingo-Castel 1991;Takahashi et al 1995).…”
Section: Introductionmentioning
confidence: 99%